MONGOLIA’S CHANCES IN EAST ASIAN CULTURAL RELATIONS AND EXCHANGE - Udo B., Barkmann (Acta Mongolica, 2011)
The geopolitical position of democratic Mongolia can certainly be considered to be unrivalled. Enclosed by Russia in the North and by China in the South, both neighbour countries being closely interrelated through a strategic partnership and the Shanghai Cooperation Organization (SCO), Mongolia did not only manage to create relations of good neighbourhood and friendship with both of them, but a strategic partnership as well. Even though, her historical experiences with her two neighbours induced Mongolia to balance out and restrict their influence on her own development through “third neighbour” politics (those “third neighbours” being the U.S.A., EU, Japan, Korea, India and others). Nevertheless, it is more than understandable that the principle of good neighbour relations is what counts in her foreign politics. The flexibility of her other foreign political premises is highly dependant on the quality of these relations. On the other hand, these premises are of vital importance for Mongolia, being a landlocked country and in need of free access to the world market with respect to the exploitation of its strategic raw materials.